2020
DOI: 10.3390/metabo10090372
|View full text |Cite
|
Sign up to set email alerts
|

Succinate Is an Inflammation-Induced Immunoregulatory Metabolite in Macrophages

Abstract: Immunometabolism revealed the crucial role of cellular metabolism in controlling immune cell phenotype and functions. Macrophages, key immune cells that support progression of numerous inflammatory diseases, have been well described as undergoing vast metabolic rewiring upon activation. The immunometabolite succinate particularly gained a lot of attention and emerged as a crucial regulator of macrophage responses and inflammation. Succinate was originally described as a metabolite that supports inflammation vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 35 publications
(84 reference statements)
0
74
0
2
Order By: Relevance
“…Yet, IL-1β is associated with tumorigenesis by a direct induction of EMT [8]. Additionally, an anti-inflammatory role of succinate on macrophages has been described recently, decreasing CD86, CD80 and inducible nitric oxide (iNOS) expression and secretion of IL-6, tumor necrosis factor (TNF) and NO independently of GPR91 [68]. However, whether this mechanism also plays a role in TAM generation in vivo remains to be established.…”
Section: Succinate Induces Tumor-promoting Cytokine Production In Macmentioning
confidence: 99%
“…Yet, IL-1β is associated with tumorigenesis by a direct induction of EMT [8]. Additionally, an anti-inflammatory role of succinate on macrophages has been described recently, decreasing CD86, CD80 and inducible nitric oxide (iNOS) expression and secretion of IL-6, tumor necrosis factor (TNF) and NO independently of GPR91 [68]. However, whether this mechanism also plays a role in TAM generation in vivo remains to be established.…”
Section: Succinate Induces Tumor-promoting Cytokine Production In Macmentioning
confidence: 99%
“…Previous studies have identified immunosuppressive roles for α-ketoglutarate. Interleukin-4 (IL-4)-induced anti-inflammatory macrophages have been shown to accumulate the metabolite α-ketoglutarate [58]. It was also found that α-ketoglutarate suppresses the activation of pro-inflammatory macrophages (e.g., IL-1β expression) and supports endotoxin tolerance after activation [26,59].…”
Section: α-Ketoglutaratementioning
confidence: 99%
“…PHD1 inactivates IKK-β kinase via hydroxylation of Pro191, which, in turn, phosphorylates IκB-α, activating NF-κB [57,60]. α-Ketoglutarate inhibits stabilization of hypoxia-induced factor (HIF)-1α, a transcription factor inducing expression of immune-related genes (e.g., pro-inflammatory cytokines [61], glycolytic enzymes, and glucose transporters [62][63][64][65]) by donating an electron to HIFspecific PHD for prolyl hydroxylation leading to the degradation of HIF-1α [28,53,58,62,[66][67][68][69][70]. In line with this, reduced levels of α-ketoglutarate were found to abolish PHD activity [16,53,69,71,72].…”
Section: α-Ketoglutaratementioning
confidence: 99%
See 2 more Smart Citations